Ruma Bolon-based IPAS instruction for strengthening elementary students' critical thinking skills - Eka Margareta Sinaga; Nova Florentina Ambarwati; Ahmad Sudito Sihotang (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study examines how Ruma Bolon-based IPAS instruction can strengthen elementary students' critical thinking skills while sustaining Toba Batak cultural values as learning resources. Using an explanatory mixed-methods design, the study involved 30 fourth-grade students in Medan Helvetia District. Quantitative data were gathered through a validated critical-thinking test, supported by interviews, classroom observations, questionnaires, and documentation. Instrument validation showed strong content validity (CVI = 0.91), valid item coefficients (0.42-0.81), and high reliability for the critical-thinking test (Cronbach's alpha = 0.88) and student perception questionnaire (Cronbach's alpha = 0.86). The quantitative findings showed increases in analytical skills from 40% to 70%, synthesis skills from 50% to 75%, and evaluation skills from 60% to 80%; the average score rose from approximately 65% to 85%. A paired-sample t-test confirmed the improvement, t(29) = 16.84, p < 0.001, with a large effect size (Cohen's d = 1.92) and a normalized gain of approximately 0.60. Qualitative findings indicated that Ruma Bolon symbols, spatial organization, and values such as cooperation and social harmony helped students relate IPAS concepts to familiar cultural experiences. The integration of local culture made classroom discussion, project work, and evaluation tasks more meaningful. These findings suggest that culturally grounded IPAS instruction can support critical thinking, creativity, and cultural appreciation when it is designed through clear learning indicators and valid assessment procedures.